Reusable Manganese Catalyst for Site‐Selective Pyridine C−H Arylations and Alkylations. Issue 50 (29th July 2021) - Choi, Isaac; Shen, Zhigao; Ronge, Emanuel; Karius, Volker; Jooss, Christian; Ackermann, Lutz
Abstract: Herein, we disclose a recyclable, hybrid manganese catalyst for site‐selective azine C−H activation by weak amide assistance. The novel, reusable catalyst enabled C3–H arylation and C3–H alkylation with ample scope, and was characterized by detailed transmission electron microscopy analysis. Abstract : A recyclable hybrid‐manganese catalyst was developed for site‐selective azine C−H activation by weak amide‐assistance with ample substrate scope. The heterogeneous catalyst proved to be reusable, and was analyzed in detail by spectroscopy, spectrometry and transmission electron microscopy.